The Public-Private Partnership in the infrastructure of the Netherlands and the Czech Republic - Procházková, Alena (2012)
In the Czech Republic, half of the infrastructure network is still missing. Moreover, in the past, Dutch and Czech road infrastructure projects have been delivered over-budget and rarely on schedule. Despite a weak fiscal position in the Czech Republic there is still a need for infrastructure investments. Solution for mentioned issues can become the realization of the Public-Private Partnership (PPP) projects. The features (for instance the payment mechanism) of Public-Private Partnership (PPP) projects not only make these investments possible but also solve other problems mentioned. Both the Netherlands (NL) and the Czech Republic (CR) have already established an environment enabling PPP implementation (e.g. established PPP Units, methodologies, dealing with legislation); But despite many PPP projects being carried out on the municipality level, there is not even one PPP project being implemented on the national level in the CR. This is in contrast to the NL, where there is already a developed PPP market, and there is investment in several new national projects every year. How can the CR improve its PPP implementation policy? The answer to this question provides the final recommendations based on the Dutch PPP practice within this Master's thesis. Learning from mistakes of the other countries, in this case it is the Netherlands, may provide for higher effectiveness in the PPP implementation and in the faster adaptation or improvement of the current partnerships. To elaborate the thesis it has been used interviews, questionnaire and several primary and secondary sources, that have been available in czech, dutch and english languages.